Performance analysis of orthogonal frequency division multiplexing-based terahertz communication system - Lim, Lincoln (Nanyang Technological University, 2024)
Orthogonal frequency division multiplexing (OFDM) stands as a pivotal technology across a multitude of wireless standards, solidifying its significance in various application deployments. This paper aims to ascertain the ergodic capacity of an OFDM system operating in conjunction with diverse wireless channels, spanning from simpler models such as Rayleigh and Rician to more intricate models like Nakagami-m and alpha - mu channels, respectively.